X‐linked inhibitor of apoptosis protein represents a promising therapeutic target for relapsed/refractory ALL - Michela Carlet; Karin Schmelz; Jenny Vergalli; Tobias Herold; Daniela Senft; Vindi Jurinovic; Thomas Hoffmann; Jutta Proba; Nina Weichert; Christian Junghanß; Mareike Roth; Georg Eschenburg; et al. (EMBO Molecular Medicine)
Abstract Acute lymphoblastic leukemia (ALL) represents the most frequent malignancy in children, and relapse/refractory (r/r) disease is difficult to treat, both in children and adults. In search for novel treatment options against r/r ALL, we studied inhibitor of apoptosis proteins (IAP) and Smac mimetics (SM). SM‐sensitized r/r ALL cells towards conventional chemotherapy, even upon resistance against SM alone. The combination of SM and chemotherapy‐induced cell death via caspases and PARP, but independent from cIAP‐1/2, RIPK1, TNFα or NF‐κB. Instead, XIAP was identified to mediate SM effects. Molecular manipulation of XIAP in vivo using microRNA‐30 flanked shRNA expression in cell lines and patient‐derived xenograft (PDX) models of r/r ALL mimicked SM effects and intermediate XIAP knockdown‐sensitized r/r ALL cells towards chemotherapy‐induced apoptosis. Interestingly, upon strong XIAP knockdown, PDX r/r ALL cells were outcompeted in vivo, even in the absence of chemotherapy. Our results indicate a yet unknown essential function of XIAP in r/r ALL and reveal XIAP as a promising therapeutic target for r/r ALL.